(x-8)+(5x)=(9x-80)

Simple and best practice solution for (x-8)+(5x)=(9x-80) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-8)+(5x)=(9x-80) equation:


Simplifying
(x + -8) + (5x) = (9x + -80)

Reorder the terms:
(-8 + x) + (5x) = (9x + -80)

Remove parenthesis around (-8 + x)
-8 + x + (5x) = (9x + -80)

Combine like terms: x + (5x) = 6x
-8 + 6x = (9x + -80)

Reorder the terms:
-8 + 6x = (-80 + 9x)

Remove parenthesis around (-80 + 9x)
-8 + 6x = -80 + 9x

Solving
-8 + 6x = -80 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-8 + 6x + -9x = -80 + 9x + -9x

Combine like terms: 6x + -9x = -3x
-8 + -3x = -80 + 9x + -9x

Combine like terms: 9x + -9x = 0
-8 + -3x = -80 + 0
-8 + -3x = -80

Add '8' to each side of the equation.
-8 + 8 + -3x = -80 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = -80 + 8
-3x = -80 + 8

Combine like terms: -80 + 8 = -72
-3x = -72

Divide each side by '-3'.
x = 24

Simplifying
x = 24

See similar equations:

| 14=5n+4+5n | | 7(x+5)+6(x-1)=-10 | | 3.9-30= | | X-4-20x=-2 | | 6x^2-4x-20=14 | | X+3*4= | | X^2+13x+36=36 | | 54=27x | | 2x-4+12=8(x+1-2x) | | 45/(4+1)=18-49*(3+2) | | 5x+y+3=3 | | 4t^2-4t-8=0 | | 2y+x=110fory | | c=5a+b | | 2(x+6)=4(x+2.6) | | x-.4=.4x | | 45/(4+1)= | | -4(5a-10)=0 | | f(x)=27x | | 60c-54c+108=0 | | 2x-4+12=8(x+1)-2x | | x^2+169-12=0 | | -5+7(x+6)=x+37 | | (x+2)4=8 | | 15x^2+16x+7=0 | | 33-(x+5)=8x-8 | | d=18+-27 | | (4b+3c)(5b+2c)=0 | | 200=2x+100 | | 2x+5x-9=5 | | 5(d+1)-3=32 | | 5x+4-4X=12whatisx |

Equations solver categories